FinTech loans, self-employment, and financial performance - Douglas J. Cumming; Ahmed Sewaid (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
Leveraging data from a leading FinTech peer-to-peer lending platform in the United States, allowing us to capture both individuals' successful and unsuccessful loan applications, we test the effect of FinTech loans on subsequent employment choice and future financial performance of serial borrowers, those repeatedly soliciting loans on the platform. An analysis of 198,984 loan requests made by 92,382 individuals shows that a failed loan application increases the probability of switching employment status. Self-employed individuals are 22% more likely to switch to becoming an employee following an unsuccessful loan application. This probability increases to 31% for those in the lowest income decile and decreases to 13% for those in the highest income decile. We document an improvement in monthly income and credit access following a successful loan application. However, this enhancement is asymmetric. Monthly income enhancement is 3.11 times larger for self-employed individuals in the lowest income decile relative to individuals in the highest income decile. Access to credit enhancement is 1.85 times larger for self-employed individuals in the lowest credit access decile relative to individuals in the second highest credit access decile.
Keywords: 330